AN ANALYSIS OF ERRORS MADE BY THE FIRST GRADE STUDENTS OF SMAN 1 KANDIS - Emi Cansisni; Syofia Delfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : This research was conducted to find out and analyze errors made by students in writing recount text. The method is qualitative descriptive. To describe the errors, the writer classified the errors based on Betty S. Azar’s classification (1989) they are singular plural, word form, word choice, verb tense, add a word, omit a word, word order, incomplete sentence, spelling, punctuation, capitalization, article, meaning not clear, and run on sentence. The research was conducted at SMAN 1 Kandis, the population is the first grade students of SMAN 1 Kandis with the total 202 students and the sample was X IPA 2 with 30 students. The instrument in collecting the data were test and interview. The test was writing test in which the students were asked to make recount text based on their unforgettable experience. The texts written by students were analyzed by three raters and the result was triangulated with the result of interview with the English teacher. The interview is about what teacher gets when teaching the same or not. After that, the teacher was asked to make rank about errors from the highest to the lowest errors. The result of the research shows that the highest error is capitalization with the total 158 or 26%. And the lowest is run-on sentence with the total 7 or 1,1 %. Based on the study, students are recommended to improve their understanding about writing by strengthening their knowledge starting from pay attention to all aspects that affect writing and do more practice.Key words: Error Analysis, Recount text, Writing